Hadith Critics Categories in The Selection of Hadith Narrators: A Comparative Analysis - Ridho Ilahi, Muhammad Barnaba; Razi, Fahrur; Maulana, Afif; Najib, Babun (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
The abundance of scholarly approaches within the field of hadith studies, particularly disciplines like the science of criticism and verification (jarh wa ta’dil), utilized for classifying the authenticity of a hadith, underscores the significance of discerning between the soundness of the content (matn) and the reliability of the chain of narrators (sanad). In response to this phenomenon, hadith scholars have undertaken comprehensive critical examinations encompassing both the matn and sanad without neglecting their interrelationship. Within the realm of hadith scholarship, the evaluation of the sanad serves as a yardstick for assessing the validity of a hadith, whereby the authenticity of the sanad, untainted by disparagement (jarh), plays a pivotal role in determining the reliability of the hadith. In this study, a quantitative methodology has been employed as supplementary data for a library-based research approach. This choice is justified by the existence of disparate viewpoints among categories of hadith critics, which contribute to the determination of hadith authenticity. Each category of hadith critic adheres to specific criteria when ascertaining the soundness of a hadith. Accordingly, this article delves into an in-depth exploration of the different groups of critics of hadith narrators. The aim is to caution against hastily passing judgments on potentially weak hadiths, preventing their outright dismissal or preclusion as sources of legal evidence (dalil syari).